Aboriginal sovereignty, 'crime' and criminology. Issue 1 (2nd January 2019) - Porter, Amanda
ABSTRACT: This is a review essay of Chris Cunneen and Juan Tauri's Indigenous Criminology, the publication of which coincides with a series of scandals and mounting inquiries into Indigenous justice issues around the globe. The publication of this important and timely work warrants reflection on the place of Indigenous issues within Australian criminology and their importance for the development of global criminologies. In the face of rising Indigenous incarceration rates, criminologists must ask some unsettling questions: has criminology as a discipline failed Indigenous Peoples? And, if so, how can we do things differently? To what degree has criminology been complicit in the rising rates of Indigenous incarceration internationally? And what, if anything, does criminology have to offer the crises in criminal justice which have been the experience of Indigenous Peoples around the globe?